Mendekarbonisasi Negara Berkembang: Analisis Sistematis Nexus Green Government dan Green Finance dalam Mitigasi Perubahan Iklim - Khilman Syahputra; Christ Valentino; Fahri Choiri Sinaga; Clevy Yesayas; Arina Romaina; Ardieansyah Ardieansyah; Luthfi Azhari (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Climate change presents a crucial development economics challenge, especially in Emerging Markets and Developing Economies (EMDEs), which face a massive climate finance gap. This article aims to systematically analyze the nexus between Green Government and Green Finance as a decarbonization solution. Using a Systematic Literature Review (SLR) methodology, this study synthesizes 52 peer-reviewed articles from Scopus and Sinta (2020-2025). Qualitative content analysis was used to map instruments, effectiveness, and implementation barriers. Findings show that the effectiveness of Green Finance instruments (e.g., Green Bonds) is empirically conditional upon a credible Green Government framework (e.g., third-party certification). However, this nexus is fundamentally broken in many EMDEs. Advanced governance instruments (like GPP and CBT) face an "implementation paradox," being too complex for low-capacity states. Analysis of innovations (like Green Sukuk in Indonesia) also identifies governance, not capital availability, as the main barrier. The article identifies a "vicious cycle": EMDEs' structural barriers (corruption, informality, low capacity) hinder effective Green Government. This governance failure prevents de-risking, causing 95% of global Green Finance to concentrate in developed nations. We conclude that policy interventions must shift from focusing on financial instruments to fixing fundamental governance preconditions.